HUBUNGAN RIWAYAT KEBIASAAN MEROKOK DENGAN KEJADIAN BRONKITIS DI PUSKESMAS MUARASIPONGI TAHUN 2019-2020 - Nilas Warlem; Irwan Triansyah; Ghaniyyatul Khudri; Kurnia Maidarmi Handayani; Siti Halimah (Yayasan Nusantara Hasana Berdikari, 2023)
One of the diseases of the lungs is bronchitis. Bronchitis arises as a result of exposure to infectious and non-infectious agents (especially tobacco cigarettes). Smoking is one of the main causes of bronchitis. The increased risk of mortality due to bronchitis is almost directly proportional to the number of cigarettes smoked daily. Data on smoking incidents in Indonesia is quite high. Riskesdas Data in 2018, the proportion of smoking in the population aged ≥10 as much as 24.3%. The highest proportion in Lampung province is 28.1% and the lowest in Papua Province is 18.8%. Province of North Sumatra has a proportion of i22.4%. This research to knowing the relationship of smoking habit with bronchitis incidence in Muarasipongi Health Center Mandailing Natal Regency in 2019-2020. The scope of this research is the science of pulmonary disease. The research was conducted at Muarasipongi Health Center from September 2020 to July 2021. This type of research is descriptive analytics with a Cross Sectional design approach. The affordable population in this study was patients diagnosed with Bronchitis at Muarasipongi Health Center in 2019-2020 with 66 samples using simple random sampling techniques and data analysis using fisher exact test with spss version 24 program. The most gender in bronchitis patients was male at 38 people (57.6%), the age in bronchitis patients was the most late adolescents and seniors were 13 people each (19.7%), smoking history in bronchitis patients most smoking is 40 people (60.6%), there is a relationship of smoking habit with the incidence of bronchitis in Muarasipongi Health Center Mandailing Natal Regency in 2019-2020 the value of p = 0.000. There is a relationship between smoking habit and bronchitis in Muarasipongi Health Center in Mandailing Natal Regency in 2019-2020.